Wasabia koreana Nakai: A Preliminary Study on Nutrients and Chemical Compounds That May Impact Sensory Properties - Da-Som Kim; Hoe Sung Kim; Jookyeong Lee; Jeong Hoon Pan; Young Jun Kim; Jae Kyeom Kim; Seongmin Woo; Eui-Cheol Shin (Molecules, 2018)
In this study, the nutritional, functional, and chemical measurements of sensory attributes of different parts of wasabi, namely, leaf, petiole, and rhizome, were investigated. Proximate composition analysis showed the presence of high amounts of carbohydrates in the rhizome and amino acid composition analysis confirmed high proportions of glutamic acid and aspartic acid in all three parts. While proximate composition showed low lipid content in wasabi, ω-3 fatty acids accounted for a high proportion (>44%) of the total lipids. Wasabi leaves had high vitamin C and total phenolic contents, and thus demonstrated antioxidant capacity. Allyl isothiocyanate, which gives wasabi its characteristic pungent taste, was identified by gas chromatography/mass spectrometry and an electronic nose. On an electronic tongue, wasabi leaves showed compounds associated with sourness and saltiness while the petiole had high content of compounds associated with sweetness and bitterness. This study provides basic data for the utilization of wasabi parts as food materials based on their nutritional, functional, and chemical measure of sensory attributes.